The Effect of Video-Based Diabetes Self-Management Education (DSME) Telenursing on Level of Knowledge in Diabetes Mellitus Patients - Ervina Yanti Harahap; Abdul Muhith; Akas Yekti Pulih Asih; Siti Nur Hasina (Universitas STRADA Indonesia, 2025)
Background: Diabetes mellitus remains a major health problem, characterized by high prevalence and complications due to low patient knowledge about self-management. Effective education is needed to enable patients to manage their diabetes independently. The use of innovative educational media, such as telenursing-based videos, is considered to increase the effectiveness of knowledge and skills transfer, thus supporting improved knowledge levels among diabetes patients. Video-based Telenursing Diabetes Self-Management Education (DSME) can facilitate increased knowledge so that the self-care behavior of DM sufferers can increase. Purpose: The aim of the research was to analyze the effect of video-based telenursing diabetes self-management education (DSME) on the level of knowledge of Diabetes Mellitus patients. Methods: This research design was quasi-experimental with a pretest posttest approach with control group design. The population is all DM patients. The sampling method was accidental sampling of 60 respondents who were divided into 30 intervention groups and 30 control groups. The video-based DSME telenursing intervention was applied 2 times a week for 2 weeks to the intervention group, while the control group only carried out their usual routine. The instrument used was the DKQ-24 (Diabetes Knowledge Questionnaire) questionnaire. Data analysis used Wilcoxon Signed Rank with a significance value of α = 0.05. Results: The results of the research on the knowledge variable showed that the p value was 0.000 < 0.05, meaning that there was an influence of video-based DSME telenursing on the level of knowledge of DM patients in the intervention group. Conclusion: The application of video-based telenursing diabetes self-management education (DSME) affects the level of knowledge of Diabetes Mellitus patients. Nurses are expected to be able to implement video-based DSME telenursing so that patient self-care increases and can prevent complications.